Pemanfaatan Limbah Lumpur IPAL Proses Biologi Sebagai Bahan Bakar Alternatif dalam Bentuk Briket - Aldy Darmansyah Putra; Wildan Nurfalah; Emma Hermawati Muhari; Muchtar Gozali (Department of Chemical Engineering, Politeknik Negeri Bandung, 2022)
Industrial WWTP sludge has not been used properly, especially biological process WWTP sludge can be used as an alternative fuel in the form of briquettes. The purpose of this study was to determine potential utilization of biological process WWTP sludge as briquettes, and to determine the effect of adding variations charcoal to the quality of briquettes. The biological process WWTP sludge was obtained from the Trio Food, Cianjur. The dried sludge has a calorific value 2468 cal/g. The research methodology includes material drying, size reduction (250 μm), mixing, molding, and briquette drying. Briquettes are made with variations in the addition of 30%, 40%, 50%, 60%, 70% charcoal. The results of the study showed that the addition of charcoal resulted increase in the water content, fixed carbon, and calorific value of briquettes as well decrease in ash content, and volatile matter. The highest calorific value in the variation of the addition charcoal is 70% at 3819 cal/g, the value still does not meet SNI 1/6235/2000 (standard for wood charcoal briquettes). The biological process WWTP sludge has potential to be used as fuel in the form of briquettes with the addition of coconut shell charcoal and carbonized coal.